2018
DOI: 10.1002/ijc.31536
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐diagnostic blood immune markers, incidence and progression of B‐cell lymphoma and multiple myeloma: Univariate and functionally informed multivariate analyses

Abstract: Recent prospective studies have shown that dysregulation of the immune system may precede the development of B‐cell lymphomas (BCL) in immunocompetent individuals. However, to date, the studies were restricted to a few immune markers, which were considered separately. Using a nested case–control study within two European prospective cohorts, we measured plasma levels of 28 immune markers in samples collected a median of 6 years before diagnosis (range 2.01–15.97) in 268 incident cases of BCL (including multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…Notably, a composite angiogenesis marker score based on levels of these three markers substantially improved our ability to predict absolute risk of progression from MGUS to MM beyond criteria in the current Mayo risk stratification model,(2-4) particularly during the first five years of follow-up. Two recent prospective studies with fewer MM cases (N=76 and 65, respectively) identified several immune markers that were inversely associated with MM risk (19,20); however, these studies did not evaluate most of the markers that we found to be positively associated with MM risk and MGUS progression to MM, and other overlapping markers (e.g., FGF-2, VEGF, TGF-α) did not reach statistical significance in our analyses.…”
Section: Discussioncontrasting
confidence: 69%
“…Notably, a composite angiogenesis marker score based on levels of these three markers substantially improved our ability to predict absolute risk of progression from MGUS to MM beyond criteria in the current Mayo risk stratification model,(2-4) particularly during the first five years of follow-up. Two recent prospective studies with fewer MM cases (N=76 and 65, respectively) identified several immune markers that were inversely associated with MM risk (19,20); however, these studies did not evaluate most of the markers that we found to be positively associated with MM risk and MGUS progression to MM, and other overlapping markers (e.g., FGF-2, VEGF, TGF-α) did not reach statistical significance in our analyses.…”
Section: Discussioncontrasting
confidence: 69%
“…As detailed in the Supporting Information, we ran a series of linear mixed models for each disease‐related adduct and each of the 2,670 smoking‐related CpG, setting the methylation level as the variable of interest. These models also accounted for technical variation in the methylation data using a two‐step strategy first estimating, and second removing technically‐induced shifts in measured methylation levels . Results from these analyses were visualized as a bipartite network where edges were selected based on statistical significance of the pairwise associations, correcting for 2,670 tests.…”
Section: Methodsmentioning
confidence: 99%
“…These models also accounted for technical variation in the methylation data using a two-step strategy first estimating, and second removing technically-induced shifts in measured methylation levels. 22,29,33 Results from these analyses were visualized as a bipartite network where edges were selected based on statistical significance of the pairwise associations, correcting for 2,670 tests.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Recently, dimension reduction techniques, such as sPLS, have also been extended to take into account functional grouping within the omics such as gene pathways, or metabolic function. For example, this tool was applied to identify the predictive power of prediagnostic levels of inflammatory markers in patients with B-cell lymphomas to select the most relevant protein groups in relation to disease status [85]. When considering the internal exposome as a mediator of the external exposome-health outcome, approaches such as the meet-in-the-middle approach may be useful, i.e., identifying biomarkers linking exposures and disease outcomes [86].…”
Section: Incorporating Omics Into Exposome Researchmentioning
confidence: 99%